2020
DOI: 10.1556/034.62.2020.1-2.4
|View full text |Cite
|
Sign up to set email alerts
|

The amount of lichen secondary metabolites in Cladonia foliacea (Cladoniaceae, lichenised Ascomycota)

Abstract: The terricolous species Cladonia foliacea (Cladoniaceae, lichenised Ascomycota) widely distributed in open, dry lowland steppe and rocky mountain grassland vegetation in Europe was chosen as a potential test organism for ecological experiments, since their thalli are producing cortical solar radiation-protective and UV screening pigment dibenzofuran usnic acid and medullary secondary substance depsidone fumarprotocetraric acid. Significant seasonal differences were found in the amounts of lichen secondary meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Therefore, we can conclude that it is possible to apply C. foliacea as a test lichen for acetone rinsing experiments; however, the extraction efficiency of its lichen compounds needs to be quantified (cf. Farkas et al 2020). Lichen species with coccoid green-algal (Trebouxia sp.)…”
Section: Viability Based On F V /F M Measurementsmentioning
confidence: 99%
“…Therefore, we can conclude that it is possible to apply C. foliacea as a test lichen for acetone rinsing experiments; however, the extraction efficiency of its lichen compounds needs to be quantified (cf. Farkas et al 2020). Lichen species with coccoid green-algal (Trebouxia sp.)…”
Section: Viability Based On F V /F M Measurementsmentioning
confidence: 99%
“…The difference is explained by the high natural variation of the concentrations of LSMs in lichen thalli ranging from c. 0.1% to 10%(-30%) of their dry weight [17]. The larger necessary concentration of the crude extract is explained by the amount of the LSM present in the thallus [49].…”
Section: Discussionmentioning
confidence: 97%
“…Research has suggested photoprotection activity for usnic acid [52] and facilitation in exploiting low light intensities for atranorin [63]. This can explain their correlations with vascular plants which produce a thicker canopy than herbs and forbs, i.e., chamephytes and phanerophytes, which occur in mature stages of dry grasslands.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them show cytotoxic activity and are much studied for their pharmacological potential [ 17 , 18 , 19 ], but their ecological roles have been addressed more rarely. More investigated are allelopathic [ 44 , 45 , 46 ] and anti-herbivorous [ 47 , 48 , 49 ] effects, rarer are ecological studies that investigated their roles in photoprotection [ 50 , 51 , 52 ] and in regulating species’ preferences for substrate pH [ 20 , 21 , 22 , 53 ].…”
Section: Methodsmentioning
confidence: 99%